An observational study to assess obstetric services trends among pregnant women registered at a health centre of Chandigarh city - Sharma, Munish Kumar; Gour, Neeraj; Thakare, Meenal; Goel, N. K.; Chaudhary, Meenakshi (International Journal Of Community Medicine And Public Health, 2018)
Background: Maternal and child healthcare services are very important for the health outcomes of the mother and that of the child by ensuring that both maternal and child deaths are prevented. Present study has been planned to study the trend of utilization of antenatal care services among women registered at field practice area of Government Medical College & Hospital, Chandigarh. Methods: Secondary data of pregnant women registered at field practice area of Government Medical College & Hospital, Chandigarh has been collected from records of respective health set up. Data has been analyzed to find out trend of different ANC service indicators like year of registration, season of registration, TT immunization, Parity, his risk behavior of pregnancy, JSY registration, MTP (medical termination of pregnancy), hemoglobin level etc. Results: Out of all registration trend of registration of new pregnancy was almost similar during all four years (2013-2017). Although after careful analysis of data it more in rainy season (10.1%) in year 2013-14 whereas summer season reported more new pregnancies (10.4%) in the year 2016-17. out of total doses received of TT 1st dose among all reported pregnant women majority of doses (11.9%) received in summer season of year 2016-17 followed by 9.2% in rainy season of year 2013-14. Number of registration of pregnant women was almost equal among all years of registration. Conclusions: It provides future direction to conduct more such studies to find out trend considering some public health related correlates. Simultaneously it also urges researchers to find out reasons of such trends in a bid to make results more applicable.